Metabolic Profile of Offspring from Diabetic Wistar Rats Treated with Mentha piperita (Peppermint) - Barbalho, Sandra M.; Damasceno, Débora Cristina [UNESP]; Machado Spada, Ana Paula; da Silva, Vanessa Sellis; Martuchi, Karla Aparecida; Oshiiwa, Marie; Farinazzi Machado, Flavia M. V.; Mendes, Claudemir Gregorio (Hindawi Publishing Corporation, 2011)
This study aimed at evaluating glycemia and lipid profile of offspring from diabetic Wistar rats treated with Mentha piperita (peppermint) juice. Male offspring from nondiabetic dams (control group: 10 animals treated with water and 10 treated with peppermint juice) and from dams with streptozotocin-induced severe diabetes (diabetic group: 10 animals treated with water and 10 treated with peppermint juice) were used. They were treated during 30 days, and, after the treatment period, levels of glycemia, triglycerides, total cholesterol, and fractions were analyzed in the adult phase. The offspring from diabetic dams treated with peppermint showed significantly reduced levels of glucose, cholesterol, LDL-c, and triglycerides and significant increase in HDL-c levels. The use of the M. piperita juice has potential as culturally appropriate strategy to aid in the prevention of DM, dyslipidemia, and its complications.